TEKNIK DAN TAKTIK PENYIDIK DALAM PENETAPAN TERSANGKA PADA TINDAK PIDANA PORNOGRAFI MELALUI INTERNET (Studi Pada Direktorat Reserse kriminal Khusus Polda Sumbar) - JL, Jamaldi; Ferdi, Ferdi (LPPM Universitas Ekasakti Padang, 2019)
The pornography crime through the internet is regulated in Article 27 paragraph (1) of the ITE Law. The difficulty in investigating is collecting evidence to determine suspects from pornography crimes through the internet. This research is legal research with analytical descriptive specifications. The results of the study show that the investigator's technique and tactics in determining suspects in pornography crimes through the internet is by first proving the existence of errors or elements of harmony from the person who became an actor in the pornographic video and the mistake of the perpetrator who recorded and distributed the video. There is a possibility that the two involved can be made suspects. The obstacle in determining suspects in pornography is that there are no witnesses who know directly.